Gender, Technology, and the World of Work: Exploring the Digital Divide Among Female Workers - Inayah Inayah; Diana Maghfiroh (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The digital revolution has significantly reshaped the global labor market, yet its benefits remain unequally distributed—particularly along gender lines. Women in many regions face considerable barriers in accessing digital tools, acquiring digital literacy, and participating in digital economies. This research aims to explore the gendered digital divide in the world of work by identifying patterns of inequality, understanding underlying socio-cultural and institutional factors, and proposing inclusive solutions. A mixed-methods approach was adopted, combining a structured survey (n=1,500 across three countries) with in-depth interviews and focus group discussions among female workers from diverse sectors and regions. Quantitative findings reveal that women consistently lag behind men in internet access, digital confidence, and participation in online labor platforms. Only 37% of women reported digital confidence at work compared to 66% of men. Qualitative insights highlight barriers such as gender norms, limited policy outreach, and insufficient institutional support. Moreover, many women are excluded from workplace decision-making in digital transformation processes. These disparities not only restrict individual economic mobility but also hinder broader development goals. The study concludes that the digital divide is both a technological and structural issue requiring holistic intervention—ranging from digital infrastructure to gender-responsive training and workplace inclusion policies. Findings support the need for national and international action to ensure that digitalization advances, rather than limits, gender equality in the labor force.